Effect of training program on heart rate variability and left ventricular function after coronary angioplasty - Amira Mohamed Abdelaziz; Azza Abdelaziz Abdelhady; Hamdy Soliman Mahmoud; Zeinab Mohamed Helmy (Cairo : Amira Mohamed Abdelaziz, 2010)
Cardiac autonomic dysfunction is associated with risk of restenosis and cardiovascular mortality in patients after percutaneous transluminal coronary angioplasty (PTCA). Anslysis of heart rate variability (HRV) is an important, widely used method for assessing cardiac autonomic regulation and also examine of left ventricular function and morphology
Thesis (Ph.D.) - Cairo University - Faculty of Physical Therapy - Department of Physical Therapy for Cardiopulmonary and Geriatrics Disorder
Issued also as CD
Keywords: Exercise tranining; Heart rate variability; Percutaneous transluminal coronary angiopasty